Barriers limiting access to healthcare among refugees or asylum seekers in Asia in the recent years: a scoping review: 10.55131/jphd/2022/200117 - Ying LIEW, Zi; Yi LIM, Shin; Hwa SHA, Kar; Thing SZE, Wei (Journal of Public Health and Development, 2022)
Over the years, the number of refugees that reside in Asian countries has been increasing. Many refugees that arrive are at risk of many diseases and comorbidities, for example, mental health diseases, trauma, malnutrition and many more. This scoping review aimed to explore the barriers faced by refugees or asylum seekers that limit their access to healthcare services in their host countries. Systematic searching was performed in PubMed and Science Direct databases to search for the relevant studies published in English from the year 2017 to the year 2020. Arksey and O’Malley’s methodology framework was adopted in this scoping review. Ten studies that addressed this topic were included. We found that lack of awareness of one’s rights to healthcare, communication, cultural differences and financial difficulties were reported as the key barriers faced by the refugees in accessing healthcare in the Asian host countries. Improvements in health promotion, communication, cultural support and financial support for the refugees settling in Asia must be urgently addressed.